Short reports - Itämies, Juhani (Entomologica Fennica, 2000)
The following reports have been presented last year at the meetings of the Entomological Society of Finland (ESF), the Societas Entomologica Helsingforsiensis (SEH), the Lepidopterological Society of Finland (LSF) or the Entomological Club of the Zoological and Botanical Society ofTurku (ECT). For biogeographical provinces, Finnish grid coordinates, and UTM squares see inside back cover of annual issues 2 and 4, respectively.